A Pilot Investigation into Targeted Muscle Reinnervation for Complex Regional Pain Syndrome, Type II. Issue 12 (22nd December 2022) - Shin, Stephanie E.; Haffner, Zoë K.; Chang, Brian L.; Kleiber, Grant M.
Abstract : Background: Complex regional pain syndrome (CRPS) is a debilitating condition, characterized by severe pain with vascular, motor, or trophic changes. Varied presentations make this a diagnostic and therapeutic challenge. There is a lack of high-quality evidence demonstrating efficacy for most existing therapies, particularly with surgical intervention for type II CRPS (CRPS-II). Targeted muscle reinnervation (TMR) is a surgical technique to transfer the terminal end of a divided nerve to a recipient motor nerve, shown to limit phantom limb pain, residual limb pain, and postamputation neuroma pain. Methods: Herein, we describe a series of 13 patients undergoing TMR for CRPS-II by a single surgeon from 2018 to 2021 in the upper (38%) and lower extremities (62%). All patients had a diagnosis of CRPS-II with either traumatic or postsurgical etiology, each seeking TMR with or without concomitant treatment to control their pain after previous therapies had failed. Three patients had previous lower extremity amputation, whereas three others received lower extremity amputation at the time of TMR, each indicated for control of CRPS pain. Results: Of the patients receiving TMR within 1 year of CRPS diagnosis, all three reported improved function, and two patients were able to tolerate a prosthetic for ambulation after previous pain prevented prosthetic use. Of the entire cohort, all but one patient reported reduced pain interference or improved function. Conclusions: These outcomes suggest that TMR may provide some benefit to reducing pain severity patients with CRPS, even after a more chronic disease course. Further prospective trials are warranted.